The Development of Prenatal Muscle Satellite Cells (MuSCs) and Their Epigenetic Modifications During Skeletal Muscle Development in Yak Fetus - Guoxiong Nan; Wei Peng; Shangrong Xu; Guowen Wang; Jun Zhang (Biology)
To investigate prenatal muscle satellite cell (MuSC) development and the associated epigenetic modifications in yak. Here, we conducted morphological and protein co-localization analyses of fetal longissimus dorsi muscle at various developmental stages using histology and immunofluorescence staining methods. Our study observed that primary muscle fibers began forming at 40 days of gestation, fully developed by 11 weeks, and secondary muscle fibers were predominantly formed by around 105 days. Throughout development, MuSCs were mainly located between the muscle fiber membrane and the basement membrane, acting as a reserve for the stem cell pool. MuSCs appeared within myotubes only during critical phases of primary and secondary muscle fiber formation. The proliferation of MuSCs gradually decreases until birth. MuSCs with 5mC modification show a trend of increasing first and then decreasing. MuSCs with 5hmC modification also present a dynamic change trend. The 41st day and 11th week are the critical periods for the changes of both. From the 11th week to around the 110th day of gestation, the modification effect of histone H3K4me3 is crucial for MuSCs during the development of the fetal longissimus dorsi muscle. Combined, our data identify key time points for yak fetal skeletal muscle growth and development and demonstrate that DNA methylation and histone modifications in MuSCs are closely related to this process, offering a valuable basis for future research into the molecular mechanisms underlying yak muscle development.